Kepemimpinan Transformasional Kepala Sekolah Dalam Pembelajaran Abad 21 Di Sekolah Dasar - Restu Rahayu; Sofyan Iskandar (Jurnal Elementaria Edukasia, 2023)
How important is the transformational leadership of school principals in elementary schools who must be able to play a role in changing educational paradigms, changing technology, curricula in dealing with today’s 21st century learning. So that school principals can identify the main areas that need to be addressed in implementing transformational leadership to deal with 21st century learning in elementary schools. The purpose of this study was to gain a better understanding of the role and influence of transformational leadership of school principals in elementary schools in facing the challenges and demands of 21st century learning. This study used the literature review method. The resultsis that the role and influence of the principal’s transformational leadership in elementary schools in facing the challenges and demands of the 21st century are very significant, including inspiring and motivating, encouraging innovation, building collaboration, building leadership skills, and strengthening the quality of education. Likewise, in the century learning can be implemented in elementary schoolswith the principle of: utilizing technology, communicating, being creative, instilling literacy, thinking critically, being innovative, and creating human learner. As well as being able to make an important contribution to the learning to create a relevant educational environment in the 21st.